The role of indigenous farming knowledge in strengthening climate resilience among smallholder farmers: a case study of rural Zimbabwe - Shingirai Mugambiwa (CV. Literasi Indonesia, 2026)
Indigenous farming knowledge remains central to the climate resilience of smallholder agriculture in rural Zimbabwe. This study examined how smallholder farmers in Mutoko and Gweru districts use indigenous knowledge to respond to rainfall variability, prolonged dry spells, rising temperatures and declining water availability. A qualitative method and exploratory design were employed. Purposive sampling was used to select 60 smallholder farmers, comprising 30 participants from each district. Data were collected through in-depth face-to-face interviews, focus group discussions and participant observation, and were analysed thematically. The findings show that farmers rely on crop diversification, crop rotation, drought-tolerant crops, early land preparation, mulching, local seed preservation, water harvesting and riverside-well irrigation to reduce climatic risks and sustain production. Indigenous knowledge was also transmitted through intergenerational learning, farmer networks and community institutions. The study concludes that indigenous farming knowledge is a dynamic resource that should be integrated equitably into agricultural extension, climate adaptation policy and rural development planning frameworks.